Addressing Ebola-related Stigma: Lessons Learned from HIV/AIDS - Mariam Davtyan; Brandon Brown; Morenike Oluwatoyin Folayan (Taylor & Francis Group, 2014)
Background: HIV/AIDS and Ebola Virus Disease (EVD) are contemporary epidemics associated with significant social stigma in which communities affected suffer from social rejection, violence, and diminished quality of life. Objective: To compare and contrast stigma related to HIV/AIDS and EVD, and strategically think how lessons learned from HIV stigma can be applied to the current EVD epidemic. Methods: To identify relevant articles about HIV/AIDS and EVD-related stigma, we conducted an extensive literature review using multiple search engines. PubMed was used to search for relevant peer-reviewed journal articles and Google for online sources. We also consulted the websites of the World Health Organization (WHO), Centers for Disease Control and Prevention (CDC), and the National Institutes of Health to retrieve up-to-date information about EVD and HIV/AIDS. Results: Many stigmatizing attitudes and behaviors directed towards those with EVD are strikingly similar to those with HIV/AIDS but there are significant differences worthy of discussion. Both diseases are life-threatening and there is no medical cure. Additionally misinformation about affected groups and modes of transmission runs rampant. Unlike in persons with EVD, historically criminalized and marginalized populations carry a disproportionately higher risk for HIV infection. Moreover, mortality due to EVD occurs within a shorter time span as compared to HIV/AIDS. Conclusions: Stigma disrupts quality of life, whether it is associated with HIV infection or EVD. When addressing EVD, we must think beyond the immediate clinical therapeutic response, to possible HIV implications of serum treatment. There are emerging social concerns of stigma associated with EVD infection and double stigma associated with EVD and HIV infection. Drawing upon lessons learned from HIV, we must work to empower and mobilize prominent members of the community, those who recovered from the disease, and organizations working at the grassroots level to disseminate clear and accurate information about EVD transmission and prevention while promoting stigma reduction in the process. In the long run, education, prevention, and a therapeutic vaccine will be the optimal solutions for reducing the stigma associated with both EVD and HIV.